2015
DOI: 10.1039/c5pp00161g
|View full text |Cite
|
Sign up to set email alerts
|

Microbial rhodopsins of Halorubrum species isolated from Ejinoor salt lake in Inner Mongolia of China

Abstract: Microbial rhodopsins are photoactive proteins that use a retinal molecule as the photoactive center. Because of structural simplicity and functional diversity, microbial rhodopsins have been an excellent model system for structural biology. In this study, a halophilic archaea that has three microbial rhodopsin-type genes in its genome was isolated from Ejinoor salt lake in Inner Mongolia of China. A sequence of 16S rRNA showed that the strain belongs to Halorubrum genus and named Halorubrum sp. ejinoor (He). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The PCR product was separated by agarose gel electrophoresis and cloned into the pT7blue vector, which is designed for simplified cloning of PCR products. The obtained DNA sequences were determined by ABI 3130/3130xl Genetic Analyzer (Applied Biosystems) . To construct a high‐expression vector of He AR, a NdeI/XhoI fragment (containing the He AR‐coding region) from pT7blue‐ He AR was inserted into suitable sites on pET21c(+) (Novagen, Madison, WI) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR product was separated by agarose gel electrophoresis and cloned into the pT7blue vector, which is designed for simplified cloning of PCR products. The obtained DNA sequences were determined by ABI 3130/3130xl Genetic Analyzer (Applied Biosystems) . To construct a high‐expression vector of He AR, a NdeI/XhoI fragment (containing the He AR‐coding region) from pT7blue‐ He AR was inserted into suitable sites on pET21c(+) (Novagen, Madison, WI) .…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequence identities of He AR with AR1 and BR are 94% and 57%, respectively. All key functional amino acid residues of BR are conserved in He AR, including the transmembrane Asp, Glu and Arg residues associated with proton transport .…”
Section: Introductionmentioning
confidence: 99%
“…aus-1 and aus-2 isolated from a lake in Western Australia by Mukohata et al [49]. Several aR homologous proteins, including aR-3 described above, have been discovered in different haloarchaeal species [50][51][52][53]. In addition, Mukohata et al successively identified two other H + -pump-like proteins belonging to a different clade from BR and aR: cruxrhodopsin-1 (cR-1) from Haloarcula argentinensis [54] and deltarhodopsin-1 (dR-1) from Haloterrigena sp.…”
Section: H + -Pumping Rhodopsins From Various Microbial Species 21 H + -Pumps In Archaebacteriamentioning
confidence: 97%